Human skeletal muscle nitrate and nitrite in individuals with peripheral arterial disease: Effect of inorganic nitrate supplementation and exercise - Barbora Piknova; Mary N. Woessner; Joaquin Ortiz deZevallos; William E. Kraus; Mitch D. VanBruggen; Alan N. Schechter; Jason D. Allen (Physiological Reports, 2022)
Abstract Skeletal muscle may act as a reservoir for N‐oxides following inorganic nitrate supplementation. This idea is most intriguing in individuals with peripheral artery disease (PAD) who are unable to endogenously upregulate nitric oxide. This study analyzed plasma and skeletal muscle nitrate and nitrite concentrations along with exercise performance, prior to and following 12‐weeks of exercise training combined with oral inorganic nitrate supplementation (EX+BR) or placebo (EX+PL) in participants with PAD. Non‐supplemented, at baseline, there were no differences in plasma and muscle nitrate. For nitrite, muscle concentration was higher than plasma (+0.10 nmol.g−1). After 12 ‐weeks, acute oral nitrate increased both plasma and muscle nitrate (455.04 and 121.14 nmol.g−1, p < 0.01), which were correlated (r = 0.63, p < 0.01), plasma nitrate increase was greater than in muscle (p < 0.01). Nitrite increased in the plasma (1.01 nmol.g−1, p < 0.05) but not in the muscle (0.22 nmol.g−1) (p < 0.05 between compartments). Peak walk time (PWT) increased in both groups (PL + 257.6 s;BR + 315.0 s). Six‐minute walk (6 MW) distance increased only in the (EX+BR) group (BR + 75.4 m). We report no substantial gradient of nitrate (or nitrite) from skeletal muscle to plasma, suggesting a lack of reservoir‐like function in participants with PAD. Oral nitrate supplementation produced increases in skeletal muscle nitrate, but not skeletal muscle nitrite. The related changes in nitrate concentration between plasma and muscle suggests a potential for inter‐compartmental nitrate “communication”. Skeletal muscle did not appear to play a role in within compartment nitrate reduction. Muscle nitrate and nitrite concentrations did not appear to contribute to exercise performance in patients with PAD.